Advocate - cooperator veritatis in the process of the nullity of marriage - MIZIŃSKI, ARTUR GRZEGORZ (Prawo Kanoniczne, 2017)
An advocate is a qualified person who meets the requirements specified in can. 1483 CIC/83, recognized by the competent authority, who was asked by a party to the process for personal assistance, involving the defense of the interests of the client in the process or defense in court. The task of the advocate in the law of the Latin Church was defined by the term munus and officium of an ecclesiastical nature. The advocate always acts, taking into account the spirit and the objectives of the canon legal order, and therefore, like other participants of the process, is obligated to cooperate with the judge in the realisation of the fundamental purpose of proceedings under canon law, which is the search for the objective truth. One of the guiding principles in the process of matrimonial nullity contained in motu proprio “Mitis Iudex Dominus Iesus”, the Code of Canon Law and the Instruction Dignitas Connubii is the principle of seeking the objective truth. To implement this principle, cooperation is required of all participants in the process, so a judge (the diocesan bishop in an abbreviated process), the parties, the defender of the marriage bond, the advocate and the promoter of justice - if he takes part in it. A special role in this cooperation is played by the advocate, who as a person competent and skilled in law will help the judge in achieving the moral certitude needed to adjudicate on a case by presenting to him already structured facts and proofs that allow him to pass an equitable judgment. Throughout the duration of the case, ranging from assistance still before the start of the trial (ordinary or abbreviated), through lodging a libellus of litigation, actions during the trial itself and after a verdict, the advocate is - even if not always necessary – a very helpful guarantor of the faithful’s right to defense. In performing his task the advocate should act primarily in the interests of the party that he is defending, but never lose sight of the truth, which should be discovered in judicial proceedings always guided by the principle of justice.